The scale of risk: conceptualising and analysing the politics of sacrifice scales in the case of informal settlements at urban rivers in Nairobi - Aalders, Johannes Theodor (ERDKUNDE, 2018)
This paper investigates the importance of scale for power dynamics in the negotiation of risks connected to urban rivers in Nairobi, Kenya. In addition to unequal distribution of wealth, global inequalities in the distribution of risk become increasingly important. Scale as a significant dimension of inequality is discussed in the context of Nairobi’s urban rivers, as water scarcity and flooding events are expected to increase and can both be observed within the highly heterogenic city of Nairobi. The paper attempts to answer the overarching question: how do contested definitions of scale influence the distribution of risks in the case of informal settlement along Nairobi’s urban rivers? This contains a conceptual, as well as an empirical dimension. Regarding the conceptual part, riskscapes are introduced and subsequently expanded to include an explicitly scalar dimension. At that, riskscapes are understood as a contemporaneous (and often contradictory) plurality of material and ideational relations that connect risks with people and the environment. A relational focus on fluidity and movement interprets scalar levels as contingent and political and thus not inherent to entities but as the product of negotiable relations. This conceptual background interfaces with the methodology of multi-sited ethnography, which inspires the method of following the river through the fragmented city of Nairobi. Applying this conceptual framing to the case of urban slum-dwellers in Nairobi, it is argued that women are discursively and materially framed to the household level, where they face the highest flooding risk. The level of the body is identified as a susceptible but often neglected scalar framing and is therefore placed in the centre of empirical scrutiny. This informs the conclusion to regard the poor female body in the case of Nairobi’s urban rivers as a sacrifice-scale where risks produced elsewhere are ‘dumped’, addressing the empirical dimension of the research question. This paper’s main contribution is the conceptual merging of the politics of risk and scale, the substantiation of this argument by a relevant case study and subsequently the spotlighting of dynamics of marginalisation through scalar negotiations of risk.